Bruce Bronzan Campaign Retreat at Morris Cabin-Shaver Lake - Watkins, Howard::::::::: (1978)
Bob Quesada, Bruce Bronzan, Linda Bronzan holding Chloe Bronzan, Ruth Wall Bruce checking notes on yellow pad